Theory after Derrida: essays in critical praxis - Kailash C. Baral (ed.); Radhakrishnan R (ed.) (New Delhi : Routledge, Taylor & Francis Group, 2009)
Contributed articles previously published in several journals on the philosophy of Jacques Derrida, 1930-2004.
Keywords: Derrida Criticism; Critical Theory; Social Sciences